The electrical characterization of Zn(Phen)q/p-type Si/Al diode with interfacial layer by current-voltage characteristics - Yakuphanoğlu, Fahrettin; Lee, Burm-Jong (Elsevier Science Bv, 2007)
The current-voltage characteristics of Zinc (II) [(8-hydroxyquinoline)(1,10-phenanthroline)] complex (Zn(phen)q)/p-type Si/Al diode with interfacial layer have been investigated. The barrier height and ideality factor of the diode were found to be 0.71 eV and 2.05. Zn(phen)q/p-type Si/Al diode shows a metal-insulator-semiconductor structure resulted from presence of series resistance and an interfacial layer. The n and OB values obtained the presence of interfacial layer are 1.02 and 0.70eV, respectively. The effect of series resistance was evaluated using a method developed by Cheung. The R-s and n values were determined from the d ln(I)/dV plot and were found to be 30.43 k Omega and 2.16, respectively. The barrier height and R-s values were calculated from the H(I)-I plot and were found to be 0.70 eV and 30.99 Omega. The density of the interface states of the Zn(phen)q/p-type Si/Al diode was calculated and was found to be an order of 10(13) eV(-1) cm(-2). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Schottky diode; interfacial state density; series resistance